Cloud-Native DevSecOps: A Framework for Secure Continuous Delivery - Nadipalli, Rajesh (International Journal of Computing and Engineering, 2023)
The shift to cloud-native architectures and continuous delivery pipelines has amplified the need for integrated, automated security practices. Traditional security models, which operate as isolated stages late in the development lifecycle, are insufficient to address the speed and complexity of modern software delivery. DevSecOps a cultural and technical shift aims to embed security into every phase of the DevOps pipeline. This paper presents a comprehensive framework for implementing DevSecOps in cloud-native environments, emphasizing secure automation, Infrastructure as Code (IaC), and continuous compliance. The proposed framework integrates static and dynamic code analysis, container and dependency scanning, identity and access management, and runtime monitoring across CI/CD workflows. I explore key tools and practices that enable policy enforcement and threat detection without hindering development velocity. A case study on Kubernetes with GitOps highlights practical implementation, while evaluations demonstrate improved security posture and reduced time-to-remediation. The framework offers a scalable, repeatable approach to secure software delivery, ensuring regulatory compliance and resilience against emerging threats. Our findings underscore the critical importance of treating security as a shared responsibility, automated and codified across the software lifecycle.